Ubiquitin-proteasome-mediated local protein degradation and synaptic plasticity - Hegde, Ashok N. (Progress in neurobiology, 2004)
A proteolytic pathway in which attachment of a small protein, ubiquitin, marks the substrates for degradation by a multi-subunit complex called the proteasome has been shown to function in synaptic plasticity and in several other physiological processes of the nervous system. Attachment of ubiquitin to protein substrates occurs through a series of highly specific and regulated steps. Degradation by the proteasome is subject to multiple levels of regulation as well. How does the ubiquitin-proteasome pathway contribute to synaptic plasticity? Long-lasting, protein synthesis-dependent, changes in the synaptic strength occur through activation of molecular cascades in the nucleus in coordination with signaling events in specific synapses. Available evidence indicates that ubiquitin-proteasome-mediated degradation has a role in the molecular mechanisms underlying synaptic plasticity that operate in the nucleus as well as at the synapse. Since the ubiquitin-proteasome pathway has been shown to be versatile in having roles in addition to proteolysis in several other cellular processes relevant to synaptic plasticity, such as endocytosis and transcription, this pathway is highly suited for a localized role in the neuron. Because of its numerous roles, malfunctioning of this pathway leads to several diseases and disorders of the nervous system. In this review, I examine the ubiquitin-proteasome pathway in detail and describe the role of regulated proteolysis in long-term synaptic plasticity. Also, using synaptic tagging theory of synapse-specific plasticity, I provide a model on the possible roles and regulation of local protein degradation by the ubiquitin-proteasome pathway.